Policy transfer and lesson drawing. The case of the pension system reform in Mexico - Jorge Enrique Culebro Moreno, Dr.Polit (Estudios Gerenciales, 2012)
The article's objective is to analyze the development and evolution of the Mexican pension reform not only as such but also of two main bodies: on the one hand, the regulator (the National Saving for Retirement) and the other, from the pension fund manager designed as a public-private partnership (PPP Manager Retirement Funds, Afore XXI). This article finds firstly, the existence of a horizontal degree of specialization and a potential lack of accountability and transparency in organizations responsible for regulating the pension system, and secondly that the presence of values that may compete in public officials in developing their roles have affected the development of a new pension system in Mexico and the performance of the regulator.